Linking corporate social responsibility, cooperation and innovation: the triple bottom line perspective - Telma Mendes; Vítor Braga; Aldina Correia; Carina Silva (Innovation & Management Review, 2023)
Purpose Drawing on the resource-based view (RBV) and knowledge-based view (KBV) theories, this study contributes to deepen the knowledge that corporate social responsibility (CSR) exerts on firms' innovation, considering the role played by cooperation. The research also seeks to ascertain the factors that influence the development of business cooperation. Design/methodology/approach The database used is the Community Innovation Survey (CIS, 2014) applied in the European Union (EU) during the time period 2012-2014. A sample of 7083 Portuguese firms were analyzed through the partial least squares structural equation modeling (PLS-SEM). Findings The results suggest that CSR positively relates with firms' innovation, and business cooperation partially mediates this relationship. The outcomes also reveal that investing in certain types of innovation activities increases the firms' willingness to cooperate. Originality/value The findings contribute to encourage an open innovation strategy as an easy and effective way to cope with rapid trends and changes, since it demonstrates the complementary between innovation and cooperation, as sources of value creation. From a triple bottom line (TBL) perspective, it also highlights that CSR must include social, economic and environmental initiatives, and should be a part of the firms' innovation strategy. As a result, managers who intend to contribute for society in the long term should plan, monitor and manage all CSR dimensions.
Keywords: 650; Cooperation; Corporate social responsibility; Eco-innovation; Innovation